Decision Support System For Employee Performance Assessment To Determine The Status Of Reward Level Operator And Foreman Using Adaptive Neuro Fuzzy Inference System (Anfis) - Irawan, sandy; Prajetno Sugiono, Judi (Jurnal Informatika UPGRIS, 2022)
Employees are required to have a good work ethic in order to advance their company. This causes many companies to motivate their employees in various ways. The general goal is for better and more stable employee performance so that it benefits the company. Rewards are given to employees who excel and are able to achieve certain targets, this is more effective in motivating employees than punishment so that it can be a source of motivation for employees to work optimally. In giving rewards, sometimes employees do not match the results of their performance and without applying good calculations. For that we need a recommendation system to support employee performance appraisal to get rewards. One of the methods used is the Adaptive Neuro Fuzzy Inference System (ANFIS) method. This method was chosen because it is able to complete employee performance appraisals based on predetermined criteria and is used as a reference in giving rewards. The amount of data obtained and will be used is a number of 537 employee data which will be divided into two data, namely training data which functions as a model of 524 data and test data which functions to test the system of 13 data. The training set uses a regression algorithm to form an employee performance appraisal model. This model is a representation of knowledge that will be used to predict the reward status of operator and foreman level employees